Practical process design for chemical engineers - Marchildon, Keith; Mody, David (John Wiley & Sons, Inc., 2025)
In-depth and practical textbook resource on chemical engineering processes, ranging from fundamentals to advanced aspects Practical Process Design for Chemical Engineers presents an extensive overview of the fundamental and advanced aspects of chemical engineering processes. Spanning 20 chapters, the book delves into various processes, equipment, and methodologies essential for modern chemical engineering, from basic principles to specific applications such as reactors, separations, and process integration. Each chapter systematically covers both theoretical concepts and practical applications, emphasizing process design, operational efficiency, environmental considerations, and safety. The book aims to equip chemical engineers with a robust toolkit for tackling diverse challenges in the industry, emphasizing innovation, sustainability, and the integration of new technologies. Unlike conventional texts that often focus primarily on established methods and theoretical fundamentals, this book actively explores innovative technologies and strategies to enhance efficiency and minimize environmental impact. Additionally, the book places significant emphasis on practical experience and real-world applications, imbuing readers not only with theoretical knowledge but also with practical skills and an understanding of industry trends. The book covers: - Creativity, choice, and decision-making in chemical engineering, emphasizing the artistic and imaginative aspects of process design - Solids processes such as size reduction, granulation, particle measurement and classification, and the conveyance of solids - Principles and methods employed to mix diverse materials such as miscible and immiscible liquids, gases with liquids, and solids with liquids or gases - Critical aspects of heat exchange in chemical processes, focusing on the heating, cooling, and phase changes of various substances - Estimation of process engineering hours With detailed discussions on process intensification and the latest developments in solvent and reactor technologies, and a focus on modern, sustainable practices alongside traditional engineering concepts, this book serves as a vital resource for students and professionals seeking to polish and hone their knowledge and practice in chemical engineering design.